Amygdala Response to Facial Expressions Reflects Emotional Learning - Hooker, Christine I. (J Neurosci, 2006)
The functional role of the human amygdala in the evaluation of emotional facial expressions is unclear. Previous animal and human research shows that the amygdala participates in processing positive and negative reinforcement as well as in learning predictive associations between stimuli and subsequent reinforcement. Thus, amygdala response to facial expressions could reflect the processing of primary reinforcement or emotional learning. Here, using functional magnetic resonance imaging, we tested the hypothesis that amygdala response to facial expressions is driven by emotional association learning. We show that the amygdala is more responsive to learning object–emotion associations from happy and fearful facial expressions than it is to the presentation of happy and fearful facial expressions alone. The results provide evidence that the amygdala uses social signals to rapidly and flexibly learn threatening and rewarding associations that ultimately serve to enhance survival.